Upaya Bela Negara Melalui Pemberantasan Pasar Gelap Pada Penjualan Smartphone Ilegal - Alisya Rahma Saebani; Risca Selfeny; Yosephine Fransisca Andriani; Irwan Triadi (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
Illegal smartphone sales in Indonesia have become a form of illegal economic activity that harms the country. This activity is unlawful as the products are often imported without payment of customs duties or taxes that should be levied, causing significant losses to the state coffers. In addition, illegal smartphones often lack an official warranty, putting consumers who purchase them at risk of financial loss in the event of damage or problems with the device. This study aims to determine the issue of law enforcement against the sale of illegal smartphones in Indonesia as well as understand the country's defense efforts in eradicating the black market in the sale of illegal smartphones. The research method used is normative juridical research method or library research. The data for this research was collected through secondary data collection, including primary, secondary, and tertiary legal materials, such as laws, books, journals, and related articles. The results show that the sale of illegal smartphones not only impacts the country's financial losses, but also increases the risk of consumers who buy them. Eradicating the black market of illegal smartphone sales is not only an economic issue, but also part of the country's defense efforts to maintain the country's economic security and protect consumer rights. This research provides in-depth insights into the issue and provides a legal foundation for further action in tackling illegal smartphone sales in Indonesia.